Taxonomic revision of the Asplenium mucronatum clade (Aspleniaceae): towards understanding a highly diverse group of ferns from the Neotropical region - Lino, Vanessa; Mynssen, Claudine Massi; Külkamp, Josimar; Reis, Atiles; Sylvestre, Lana Da Silva (Phytotaxa, 2026)
Asplenium (Aspleniaceae) is the most species-rich genus (ca. 700 spp.) of leptosporangiate ferns, with a worldwide distribution. Recent phylogenetic analyses of Asplenium have recovered the Asplenium mucronatum clade as a newly recognized lineage within the genus. This clade was recovered with 11 Neotropical species, ten of which occur in the Brazilian Atlantic Forest of southeastern Brazil, recognized as the center of richness and endemism for the group. In this study, we present a taxonomic treatment of the Asplenium mucronatum clade, including analyses of stem scales and spore morphology. We describe three new species, designate ten lectotypes, recognize two synonymized names as accepted species, and synonymize a previously accepted species. All species are described in detail, and we provide an identification key, preliminary conservation assessments, distribution maps, and additional notes.